Apoptosis-inducing Plant-based Phenolic Compounds are Effective on Leukemia Cell Lines - Soltani, Amin; Shams Abadi, Milad S.; Raeisi, Mohammad; Kouhihabibidehkordi, Golnoush; Eshaghi, Farzane; Mohreh, Omid; Rafieian-Kopaei, Mahmoud (Current Pharmaceutical Design, 2023)
Numerous natural compounds have been identified that are able to induce apoptosis in cancer cells. These compounds have various chemical properties and are found in medicinal plants, vegetables, and fruits that are commonly consumed by humans. Phenols represent important compounds, which have been demonstrated to induce apoptosis in cancer cells, and some of the involved mechanisms have also been determined. The most important and abundant phenolic compounds are tannins, caffeic acid, capsaicin, gallic acid, resveratrol, and curcumin. Induction of apoptosis with the least or no toxicity to natural tissues is one of the useful effects of many plant-based bioactive compounds. Phenols, with anticancer potency at different degrees, serve to induce apoptosis through different pathways, including both extrinsic (Fas) and intrinsic (calcium release, ROS increase, DNA degradation, and mitochondrial membrane impairment). In this review, we report these compounds and their apoptosis-inducing mechanisms. Apoptosis or programmed cell death is a precise and systematic mechanism that is aimed at removing damaged or abnormal cells and is very useful to control, treat, and prevent cancer. Apoptotic cells are characterized by specific morphological features and molecular expression. In addition to physiological stimuli, there are many external factors that can be useful for inducing apoptosis. Also, these compounds can affect the regulatory proteins of the apoptotic pathways, such as the apoptotic proteins (Bid and BAX) and antiapoptotic proteins (Bcl-2). Taking these compounds and their molecular mechanisms into account can help use them in combination with chemical drugs and develop new drugs.
Keywords: phenolic compounds